Newborn screening for sickle cell anemia in Antalya, Türkiye - Öztürk, Zeynep; Küpesiz, O Alphan; Karasu, Gülsün; Uygun, Vedat; Oygür, Nihal; Yeşilipek, M Akif (The Turkish Journal of Pediatrics, 2023)
Background. In a screening study conducted on adults, the prevalence of sickle cell traits in Antalya was found to be 0.24%. Since no screening studies have been conducted in the neonatal period in our region, the exact incidence has not been determined. In this study, we aim to report our experience of neonatal screening for sickle cell disease in Antalya, Türkiye. Methods. During a 14-month period, 2562 heel prick blood samples, taken on filter paper from Akdeniz University Hospital, Antalya Education and Research Hospital and Antalya Atatürk State Hospital and four other healthcare centers, were studied using the high pressure liquid chromatography method. Blood samples were studied using the `Sickle Cell Short Program` test method on a Bio Rad Variant device. Results. In the study, no patients with sickle cell disease were identified. Four newborns who were sickle cell carriers (0.15%) and two newborns who were Hemoglobin D carriers (0.08 %), were found. Conclusion. Considering the efficiency and cost calculations made as a result of the data obtained from our study, it was concluded that sickle cell screening would not be effective in newborns. It seems more effective and economical to screen the children of parents, who are found to be at risk for Hemoglobin S carriage as a result of premarital tests.